Adsorption‐mediated nonlinearity of critical cracking thickness in drying nanoparticle–polymer suspensions. Issue 5 (13th February 2021) - Yamamura, Masato
Abstract: We examine the critical cracking thicknesses of as‐dried colloidal TiO2 suspensions containing water‐soluble polymeric additives, above which cracks spontaneously propagate. In contrast to common observations, the critical cracking thickness increases in a nonlinear, stepwise manner as increasing the concentration of the polymeric additive in the suspension. The critical thickness diverges when the polymer content increases above a certain threshold. We demonstrate that the first and second critical cracking thickness increments are attributable to the onset of polymer adsorption and a subsequent transition in the conformations of the adsorbing polymer chains, respectively. The critical thickness profiles with respect to normalized polymer adsorption amounts at different particle diameters converged into a single master curve. These results illustrate nontrivial evaporation processes in which the various roles of polymeric additives delay cracking into thicker films.